On octahedrality and Müntz spaces - Martiny, André (MATHEMATICA SCANDINAVICA, 2020)
We show that every Müntz space can be written as a direct sum of Banach spaces $X$ and $Y$, where $Y$ is almost isometric to a subspace of $c$ and $X$ is finite dimensional. We apply this to show that no Müntz space is locally octahedral or almost square.